Controllable Loading of Noble Metal Nanoparticles on Multiwalled Carbon Nanotubes/Fe3O4 through an In Situ Galvanic Replacement Reaction for High‐Performance Catalysis. Issue 7 (19th May 2014) - Yang, Shu‐Liang; Cao, Chang‐Yan; Wei, Fang‐Fang; Huang, Pei‐Pei; Sun, Yong‐Bin; Song, Wei‐Guo
Abstract Nobel metal nanoparticle loaded carbon nanotube (CNT) composites have wide applications in heterogeneous catalysis, and the catalytic properties are largely controlled by the size, composition, and dispersion state of the noble metal nanoparticles. However, the chemically inert feature of CNTs makes it difficult to directly disperse noble metal nanoparticles in a uniform manner. In this work, by an in situ galvanic replacement reaction between Cu nanoparticles and noble metal ions, a simple and efficient strategy was developed to produce magnetic multiwalled (MW) CNTs–Fe3O4 supported noble metal nanoparticles. The MWCNTs–Fe3O4–Pd showed impressive activity in the carbonylative Sonogashira coupling reaction and in the catalytic hydrodegradation of methylene blue.